Machine Translation Research in Czechoslovakia - Hajič, Jan; Hajičová, Eva; Rosen, Alexandr (Meta, 1992)
AbstractMachine translation research activities in Czechoslovakia starting in early the 60's are outlined, together with the basics of the theoretical background on which the parsing and representation levels have been based. Two more recent systems are described in more detail: APAC, working from English to Czech on INSPEC technical abstracts, and RUSLAN, which, translating from CZECH to Russian, was heavily taking advantage of the closeness between these languages. We conclude with a short description of the current project, which emphasizes the use of text corpora in combination with (more) traditional approaches. Many of the ideas we want to elaborate in the near future are present in the current project, and a word on future plans is also added.